Poly(ADP-ribose) polymerase-1 and its ambiguous role in cellular life and death - Maria Castedo; Antoine Lafarge; Guido Kroemer (Cell Stress, 2023)
The deletion of the gene coding for poly(ADPribose) polymerase-1 (PARP1) or its pharmacological inhibition protects mice against cerebral ischemia and Parkinson’s disease. In sharp contrast, PARP1 inhibitors are in clinical use for the eradication of vulnerable cancer cells. It appears that excessive PARP1 activation is involved in a specific cell death pathway called parthanatos, while inhibition of PARP1 in cancer cells amplifies DNA damage to a lethal level. Hence, PARP1 plays a context-dependent role in cell fate decisions. In addition, it appears that PARP1 plays an ambiguous role in organismal aging.